PENINGKATAN HASIL BELAJAR MATERI PECAHAN MELALUI MEDIA VISUAL DI KELAS IV SEKOLAH DASAR - Dewi Aryanti (INOPENDAS: Jurnal Ilmiah Kependidikan, 2023)
This study aims to determine whether or not there is an increase in mathematics learning outcomes using visual media about fractions of fourth grade elementary school students. This study uses a qualitative research method with a classroom action research approach. The subjects of the research were the fourth grade elementary school students, totaling 16 students, consisting of 9 male students and 7 female students. The object of this research is the result of learning mathematics about fractions through visual media. The data collection instrument used a formative test sheet. The results of this study indicate that in the first cycle the score is 65 with an average grade of 56 so that classical learning completeness is 44%, while in the second cycle the score is 65 with an average grade of 80 reaching 100%. Based on the data obtained and the analysis from cycle I to cycle II, student learning outcomes have increased by 56%. Thus, it can be concluded that there is an increase in mathematics learning outcomes in grade IV elementary school by using visual media